THE EFFECTIVENESS OF PROJECT BASED LEARNING MODEL FOR SELF REGULATED LEARNING: A CASE STUDY OF POST-PANDEMIC ELEMENTARY SCHOOL SCIENCE LEARNING - Ekantini, Anita (UIN Sunan Kalijaga Yogyakarta, 2022)
After the COVID-19 Pandemic, face-to-face (FTF) learning was implemented in elementary schools in the province of the special region of Yogyakarta. However the implementation of online learning has left its own problems, especially related to self-regulation in student learning. Students need readaptation again after they are used to studying online for at least two years. This research aims to determine the effectiveness of the Project Based Learning (PjBL) model for Self Regulated Learning (SRL) students in science learning at Post-COVID-19 pandemic. This study uses the experimental method of Pretest-Posttest Control Group Design. The research was conducted at a Islamic elementary school in Yogyakarta in the 2021/2022 school year. The population of this study were students of class IV consisting of 4 classes namely A, B, C, and D. The samples of this study were students of class IV A, totaling 23 students as the control class and IV C, totaling 21 students as the experimental class. Selection of control and experimental classes using cluster random sampling technique. The research findings show that the PjBL model is effective in improving students' SRL in science subjects after the pandemic.